Economies of size for farrow-to-finish hog production in Kansas - Langemeier, Michael R.; Schroeder, Ted C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Economies of size measure the impact on average cost of production of increasing the size of operation. Data from 91 farrow-to- finish operations enrolled in the Kansas Farm Management Associations in 1992 were used to empirically estimate economies of size. Results indicate that average total cost and operation size are significantly correlated, and that average total cost declines as operations become larger. Results also indicate a substantial variability in costs of production between producers. In fact, costs of production between producers of a given size vary more than costs of production between operations of different sizes.
Keywords: Swine; Economies of size; Cost of production; Profitability